Diversivikasi Produk Olahan Abon Lele-Jamur Untuk Penguatan Ekonomi - Yulihartika, Rika Dwi; Afriani, Ririn; Azhari, Diah; Nurmalia, Ana (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Purpose to increase the community's capacity to process local raw materials into hygienic, high-quality shredded meat products with extended shelf life, while simultaneously enhancing product appeal through better and more informative packaging. The training was conducted in a participatory manner, involving material delivery and hands-on practice, covering shredded meat processing techniques, selecting food-grade packaging materials, designing product labels, and maintaining simple business records. Ongoing mentoring was provided to ensure that the acquired knowledge and skills could be independently applied by partners in their daily production activities. The results of the activity demonstrated an increase in community knowledge and skills in processing and packaging catfish and palm mushroom shredded meat products, as well as a heightened awareness of the importance of product quality and the added value of local commodities. The resulting shredded meat products have the potential to be developed as an alternative source of income for rural communities. Overall, this Community Service Program (PKM) activity not only has an economic impact through increased product sales value but also a social impact by encouraging community independence and empowerment, and strengthening the role of universities in supporting sustainable economic development based on local potential.